2022
DOI: 10.1007/s13384-022-00541-4
|View full text |Cite
|
Sign up to set email alerts
|

Leadership practices contributing to STEM education success at three rural Australian schools

Abstract: The limited research into leading STEM education in rural schools internationally tends to adopt a deficit view, with a focus on the poor achievement and aspirations of rural students, difficulties recruiting and retaining STEM teachers, and issues of isolation and under-resourcing. Counter to this trend, this paper reports on research investigating leadership practices shaping STEM education at three high STEM-performing rural schools. High-performing rural schools in Victoria, Australia were identified throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 31 publications
1
10
0
Order By: Relevance
“…Cooperation between universities and schools can be good for both pre-service teachers and students at the school (Fernández-Martín et al, 2020). This is also in line with what Murphy (2022) found, suggesting that one of the benefits of STEM education is that people in the STEM community work together more. When universities and schools collaborate, the lack of role models, which is usually a problem in STEM education, can be coped with (Ryu et al, 2019).…”
Section: Implementation Of Stem-tpd Outside Of Lecturessupporting
confidence: 84%
See 1 more Smart Citation
“…Cooperation between universities and schools can be good for both pre-service teachers and students at the school (Fernández-Martín et al, 2020). This is also in line with what Murphy (2022) found, suggesting that one of the benefits of STEM education is that people in the STEM community work together more. When universities and schools collaborate, the lack of role models, which is usually a problem in STEM education, can be coped with (Ryu et al, 2019).…”
Section: Implementation Of Stem-tpd Outside Of Lecturessupporting
confidence: 84%
“…Empowering STEM teaching staff is one of the principles in supporting the success of STEM education (Murphy, 2022). Therefore, in many places, the preparation of teachers to teach STEM in schools is starting to be done a lot.…”
Section: Discussionmentioning
confidence: 99%
“…This lack of access in rural communities is not unique to the US. For example, similar issues have been found within rural populations in Australia and China (see Murphy, 2022 andMurphy et al, 2007). Moreover, although rural environments are a rich context for learning science, rural students' opportunities to engage in their local communities often do not reflect traditional schooling systems in their counties (Saw & Agger, 2021).…”
Section: Rural Education In Stemmentioning
confidence: 54%
“…One of the biggest criticisms of STEM equity in rural education is how little attention it has received (Saw & Agger, 2021). The lack of attention is problematic because rural students experience many challenges, including a lack of resources due to their geographic isolation and decreased access to qualified educators, especially in mathematics and science (Murphy, 2022). Additionally, rural schools struggle to provide advanced coursework in mathematics and science, reliable internet access, and resources to encourage students in STEM fields (Ihrig et al, 2018;Marksbury, 2017;NASEM, 2021).…”
Section: Rural Education In Stemmentioning
confidence: 99%
“…In fact, analysis has shown that despite a 16% increase in the total number of Australian students reaching year 12 between 1992 and 2012, the proportion of students completing a science subject declined by approximately 5% (Kennedy et al, 2014). More recent research suggests that these trends are not being reversed, with enrolment intentions and nonmetropolitan issues being particularly acute contemporary concerns (Kennedy et al, 2020;Murphy, 2022).…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%